Tailoring excitonic light emission of two-dimensional transition metal dichalcogenides semiconductors - Feng, Shun (2019)
The newly emerged two-dimensional transition metal dichalcogenide (2D TMD) semiconductors like MoS2, MoSe2, WS2 and WSe2 have aroused great interest because of their underlying rich physics and the promising applications in optics, electronics and optoelectronics. One of the most intriguing properties is the excitonic light emission from direct bandgap in monolayer (1L) semiconductor TMDs, which is easily tailored and can be directly probed by photoluminescence (PL) spectra. This thesis endeavors optical investigation of extrinsic excitonic light emission of 1L TMDs by in-situ PL measurements and is organized in three parts. In the first part a tunable excitonic emission of WS2 upon DNA nucleobase coating is demonstrated, indicating a new type of optical sensing strategy. In the second part a practical approach to enhance valley polarization degree of trion by in-situ optical and electrical gating at 80 K is discovered and understood with theory of carrier screening effect on intervalley scattering. The third part dedicates to deterministic isolation of narrow defect bound exciton in 2D semiconductor nanodisks with accurate spatial and spectral positioning at 4.2 K. Last, future works based on chemically brightening dark excitons in TMD flakes and localized exciton phonon entanglement in TMD nanopatterns are proposed. Our works lay foundations for next generation optical biosensors, valleytronic devices and scalable quantum light sources based on excitonic light emission from 2D semiconductors.